2017
DOI: 10.1186/s12889-017-4767-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practices on intestinal schistosomiasis among primary schoolchildren in the Lake Victoria basin, Rorya District, north-western Tanzania

Abstract: BackgroundGlobally school-age children, adolescents and young adults bear the highest burden of schistosomiasis. When developing a specific intervention to improve community’s knowledge, attitudes, and practices (KAPs), existing KAPs must be taken into account. Therefore, this study was designed to determine schoolchildren’s KAPs on schistosomiasis in the study area.MethodsA cross-sectional study was conducted in Busanga and Kibuyi villages involving 513 schoolchildren. A pre-tested questionnaire was used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 22 publications
7
23
2
Order By: Relevance
“…All the 239 (100%) respondents reported that they had heard about malaria, 89.1% had heard about schistosomiasis while 87.4% had heard about STH. This is in tandem with other studies which have been done in Africa and have shown that knowledge about schistosomiasis as well as malaria and STH is very high 39,40 , but contradicts a study by Adoka and others along the shores of lake Victoria which found knowledge about schistosomiasis to be low 41 . This high knowledge is key to improvement of the health of the inhabitants of this island.…”
Section: Discussionsupporting
confidence: 50%
“…All the 239 (100%) respondents reported that they had heard about malaria, 89.1% had heard about schistosomiasis while 87.4% had heard about STH. This is in tandem with other studies which have been done in Africa and have shown that knowledge about schistosomiasis as well as malaria and STH is very high 39,40 , but contradicts a study by Adoka and others along the shores of lake Victoria which found knowledge about schistosomiasis to be low 41 . This high knowledge is key to improvement of the health of the inhabitants of this island.…”
Section: Discussionsupporting
confidence: 50%
“…Accordingly, skipping such important preventive chemotherapy in the area of high transmission for schistosomiasis may have a negative impact on the prevalence and intensity of the disease. Other factors that might have contributed to the observed high prevalence of intestinal schistosomiasis infection as reported by previous studies include close proximity of the school/village to the Lake [20,31], lack of clean and safe water supply [32], poor sanitation and hygiene [33], and low knowledge about mode of transmission and prevention of the disease [34,35]. Since the https://doi.org/10.1371/journal.pone.0228770.g003 study area has the history of receiving repeated mass praziquantel treatment, poor efficacy of praziquantel to the immature (juvenile) stage of the parasite may be another reason to explain the continued and reported high prevalence of the disease around the study area [36].…”
Section: Discussionmentioning
confidence: 91%
“…() The study showed that the schistosomiasis cognitive level among local students is still very low, which is similar to or even lower than previous studies in Tanzania, Cameroon, Senegal, Kenya and other countries. [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%